Hunting behaviour in domestic cats: An exploratory study of risk and responsibility among cat owners. Issue 1 (8th January 2019) - Crowley, Sarah L.; Cecchetti, Martina; McDonald, Robbie A.
Abstract: The potential impact of domestic cats on wildlife is the subject of growing international interest and concern. While feral cats are often the primary focus of research and debate, in many societies a substantial proportion of domestic cats are owned by private individuals. We present a typology that classifies domestic cats in relation to varying degrees of human control over their reproduction, movement, and provisioning. Understanding the perceptions and practices of cat owners will be key to identifying and mitigating any negative ecological effects of cat hunting behaviour. To investigate how cat owners perceive (a) their pets' hunting behaviour, (b) their responsibilities for managing this, and (c) the mitigation strategies available, we conducted detailed interviews with a diverse sample of cat owners in the United Kingdom. We identified a spectrum of views on hunting behaviour, from owners who perceived hunting as positive (for pest control, or as healthy cat behaviour) to those who were deeply concerned about its consequences for wild animals, their populations, and welfare. However, hunting was widely understood as a normal, natural component of cat behaviour, and owners rarely perceived a strong individual responsibility for preventing or reducing it. Those who did wish to manage hunting perceived several barriers to this, including concern that they were unable to control behaviour effectively without compromising cat welfare, doubt about the efficacy and practicality of popular mitigation measures, and unfamiliarity with alternative options. We recommend that (a) initiatives directed at changing cat owners' behaviour consider the multiple factors and competing priorities that inform their decision‐making (particularly cat health and welfare and practicality or cost of interventions); (b) researchers work collaboratively with cat owners and veterinary, cat welfare, and conservation organizations to identify effective solutions, and (c) some degree of accountability for managing problematic hunting behaviour should be promoted as a part of "responsible pet ownership" initiatives. Aplain language summary is available for this article. Abstract : Plain Language Summary